Exemplifying The India’s Recent Financial Status Based on The Estimated Union Budget Data 2020-2021 - Thenkovan Mariyappan (Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2022)
This study attempts to reveal the significance of the union budget for the promotion of economic growth and estimate the financial status of the union government in the recent year 2020-2021. This study follows the descriptive method of research to carry out the research work. Data was collected from various secondary sources such as union budget documents and budget analysis series in the finance ministry. The collected data has been tabulated and interpreted to infer the significance and growth of the public revenue and public expenditure of the government. The data was collected for the recent years 2019-2020 and 2020-21 to analyse the latest financial position of India. The government policy formulations and reforms have aimed at determining the banking system to support the flow of credit to the nation and implement monetary and fiscal incentives to sustain total demand and maintain output. The revenue expenditure of the union budget during the 2018-2019 period was Rs.2007399 crores and it was increased to Rs.2447780 crores in the 2019-2020 budget period. Similarly, the revenue expenditure has further increased to Rs.2630145, which constitutes 11.90 percent of the growth in the revised estimates during 2020-2021. The percentage share of the gross domestic product of the country was 2.4 percent in 2018-2019 and during 2019-2020 also maintained the same status. But, during the 2020-2021 budget it has been increased to 2.7 percent. In the same year, the fiscal deficit recorded as 3.8 percent and the primary deficit has been dropped down to -37.8 percent in the recent year. On the whole, the budget 2020-2021 focussed to promote economic growth based on the best allocation of resources